MODERN MONETARY UNREST: PUBLIC POLICY RESPONSES TO THE ADOPTION OF BITCOIN AS A HEDGE AGAINST SYSTEMIC FIAT INFLATION - Mu'awwanah, Uliyatul; Mursidah, Mursidah; Masithoh, Fitria Nur; Mu'awanah, Mu'awanah; Hamdi, Muhammad (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
The post-2008 crisis era, accelerated by the COVID-19 pandemic, has ushered in a permissive global monetary policy, raising essential questions about the sustainability of the fiat monetary system. This has triggered a trust deficit, fundamentally challenging what is termed the